The tragedy of Pudd'nhead Wilson - Twain, Mark. (New York : Signet Classics, 2007)
The American humorist's classic novel, depicting human nature under slavery, tells the story of two infants, one slave, one free, that were switched at birth.
Keywords: Infants switched at birth -- Fiction; Impostors and imposture -- Fiction; Passing (Identity) -- Fiction